Building New Banjos for an Old-Time World - Jones-Bamman, Richard, 1951- (Book collections on Project MUSE., 2017)
Banjo music possesses a unique power to evoke a bucolic, simpler past. The artisans who build banjos for old-time music stand at an unusual crossroads-asked to meet the modern musician's needs while retaining the nostalgic qualities so fundamental to the banjo's sound and mystique. Richard Jones-Bamman ventures into workshops and old-time music communities to explore how banjo builders practice their art. His interviews and long-time personal immersion in the musical culture shed light on long-overlooked aspects of banjo making. What is the banjo builder's role in the creation of a specific musical community? What techniques go into the styles of instruments they create? Jones-Bamman explores these questions and many others while sharing the ways an inescapable sense of the past undergirds the performance and enjoyment of old-time music. Along the way he reveals how antimodernism remains integral to the music's appeal and its making. He also delves into the omission of African Americans-the originators of the banjo-from both the instrument's popular history and the nostalgia engendered by the music, and the role contemporary banjo builders are playing to rectify this situation. Book jacket.